2009
DOI: 10.1007/s11102-009-0180-4
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of fused positron emission tomography/computed tomography in the localization of adrenocorticotropin-secreting pituitary adenoma in Cushing’s disease

Abstract: Despite the high resolution of magnetic resonance imaging (MRI) of the pituitary gland, up to 40% of cases of Cushing's disease (CD) have normal MRI. Fused images of positron emission tomography and computed tomography (PET-CT) may have a potential diagnostic role in CD in general and in such cases in particular. Objective of this study is to explore the diagnostic potential of PET-CT for localization of adrenocorticotropin-secreting pituitary adenomas in CD. PET-CT was performed in 12 cases with de novo (7 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 16 publications
2
35
1
Order By: Relevance
“…Hence, new methods should be explored. Although 18 F-FDG PET is helpful for detecting the sites of ACTH secretion, [19][20][21] Alzahrani et al 22 concluded that the positive rate of 18 F-FDG PET/CT is approximately 60% in patients with Cushing disease. As in our study, the sensitivity of 18 F-FDG PET/CT is unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, new methods should be explored. Although 18 F-FDG PET is helpful for detecting the sites of ACTH secretion, [19][20][21] Alzahrani et al 22 concluded that the positive rate of 18 F-FDG PET/CT is approximately 60% in patients with Cushing disease. As in our study, the sensitivity of 18 F-FDG PET/CT is unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…For nonfunctioning adenomas, 18F-FDG PET scans are usually negative, because of the low metabolic activity that is often similar to normal cells. However, the cells of functioning tumors may be more active and some studies report that functioning pituitary macro-and micro adenomas can show increased FDG uptake on PET [7][8][9][10]. In our patient the 18F-FDG PET-CT showed a precocious SUVmax at 6.2 becoming 8.9 in the late sequences.…”
Section: Discussionmentioning
confidence: 46%
“…1 Functional adenomas, comprising roughly 70% of PAs, 13 produce excess hormone secretion that can lead to a variety of clinical symptoms and associated syndromes. 4 The most common functional PAs, in descending order, are prolactin-secreting (prolactinomas), growth hormone (GH)-secreting, corticotropin (ACTH)-secreting, gonadotropin (LH or FSH)-secreting, and thyrotropin (TSH)-secreting adenomas. 5 The remaining 30% of PAs are classified as nonfunctional, which mainly produce symptoms due to their mass effect.…”
Section: Introductionmentioning
confidence: 99%
“…Routine laboratory studies, such as dexamethasone suppression tests, are able to definitively diagnose hormonal disorders at low cost, but suffer from low sensitivity and rates of false positives and negatives in up to 50% of cases. 4,7,8 Laboratory studies are also unable to localize the site of aberrant hormone secretion. Moreover, there may be a significant time lapse until hormone levels accrue to the point of eliciting detectable alterations in lab values, which can delay appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%